Olfactory neuroblastoma: A 35‐year experience and suggested follow‐up protocol. (4th February 2014) - Rimmer, Joanne; Lund, Valerie J.; Beale, Timothy; Wei, William I.; Howard, David
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis To validate a follow‐up protocol based on the long‐term outcomes and recurrence rates in patients who have undergone surgical treatment for olfactory neuroblastoma. Methods A prospective review of all patients treated for olfactory neuroblastoma at our institution over a 35‐year period. Results Ninety‐five patients were treated from 1978 to 2013, with craniofacial (65 patients) or endoscopic resection (30 patients). Duration of follow‐up ranged from 1 to 309 months (mean, 88.66 months). Fifty‐six patients were alive and well, and 13 were alive with recurrent disease. Twenty‐one patients had died of disease, and three had died of intercurrent disease. Overall survival was 83.4% at 5 years and 76.1% at 10 years. Disease‐free survival at 5 years was 80% and at 10 years was 62.8%. A Cox regression analysis showed orbital extension and intracranial involvement to be significant independent factors affecting outcome. Local and regional recurrence occurred after an average of 49 months but with a range of 3 to 233 months. Conclusions In our series, olfactory neuroblastoma most commonly recurred within the first 4 years but can recur very late, after 19.4 years in one case. There is currently no universally accepted follow‐up regime, but even late recurrence is eminently treatable. We therefore propose a protocol for lifelong follow‐up with both clinical examination and serial imaging, including the neck and entire intracranial compartment. Level of Evidence 4 Laryngoscope, 124:1542–1549, 2014